EFFECT OF DIVIDEND POLICY, CAPITAL STRUCTURE AND COMPANY SIZE TO COMPANY VALUE IN PHARMACEUTICAL COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Grace Sriati Mengga; Gregorius Edy; Agustinus Mantong (Universitas Kristen Indonesia Toraja, 2022)
In recent years, the COVID-19 pandemic spread to Indonesia, causing losses for most companies. However, pharmaceutical companies were able to survive the pandemic, The sector which will benefit the most from the pandemic is the pharmaceutical sector, as its sales have increased. As sales increase, stock prices, profits, dividends, and the value of the company all increase. Consequently, the goal of this research was to determine the impact of dividend policy, capital structure, and company size on the company value of pharmaceutical companies listed on the Indonesian stock exchange during the period of 2017-2021. This is a quantitative research design with a sampling technique which utilises the purposive sampling method to obtain 4 companies that meet the requirements as research samples. Multiple linear regression was used to analyze the data, with the independent variable dividend policy being measured with a measuring instrument (dividend payout ratio) DPR, Capital structure is measured using a DER (Debt to Equity Ratio) measuring instrument, company size is measured using a natural logarithm of total assets, and firm value is measured using a PBV (price to book value) measuring instrument. In the results of this research, dividend policy and company size were found to have no significant impact on company value, whereas the capital structure appears to have done.